Optimized synthesis and crystal growth by sublimation of 1,3,3-trichloroisoindolenines, key building blocks for crosswise phthalocyanines - Ayhan, Mehmet Menaf; Zorlu, Yunus; Gokdemir, Ozlem; Gürek, Ayşe Gül; Dumoulin, Fabienne; Ahsen, Vefa; Hirel, Catherine (Royal Soc Chemistry, 2014)
Among possible asymmetrically substituted phthalocyanines, ABAB derivatives remain rare. Their selective synthesis is based on the use of trichloroisoindolenines, so far remaining tedious to obtain. An optimized synthesis of 1,3,3-trichloroisoindolenine 1 and 1,3,3,6,7-pentachloroisoindolenine 2 is reported. An original crystallization method based on crystal growth by sublimation was eminently suitable regarding the air-sensitivity of these derivatives and allowed their thorough crystallographic characterization.
Keywords: Nonlinear-Optical Properties; Chemistry; Substituents; Porphyrins; Catalysts